A formulação do editorial da Gazeta do Povo : o discurso relatado na construção da opinião - Gaiotto, Paulo Alexandre (2006)
Editorials, as a rule, are texts by which the newspaper board propagates its official opinion on a wide range of themes. The formulation of opinions in editorials of the newspaper Gazeta do Povo and whether discourse has an important role in its constitution are analyzed. Through the analysis of the functionality of quotes in text construction current research shows that the forms of other voices differentiate the elaboration of the newspaper's editorials. Forty-one editorials on Brazilian economical growth, published between June 1 2004 and 29 January 2006, make up current research corpus. Discourse is evaluated as from the analysis of the enunciation and journalistic language through a survey of incidences in direct speech, indirect speech, second discourse, commentary on discourse, inverted commas and dicendi verbs within the context of their function in the text construction. Results show that in newspaper media there is a novel perspective in the construction of editorials. Although the researched corpus represents few editorials (a mere seven) that fit the model suggested by essay and style handbooks of Brazilian newspapers, most (thirty-four) foreground the use of the discourse in the formulation of opinion as an innovation in current textual genre. This discourse actually underpins the opinion that the editorial writer wishes to convey.